EXPERIMENTAL STUDY OF THE NEUROTOXIC EFFECTS OF PHOTODYNAMIC THERAPY ON THE SPINAL CORD - COSTA,HERTON RODRIGO TAVARES (2019)
ABSTRACT Objective To evaluate the effects of photodynamic therapy (PDT) on the dura mater using the photosensitizers aluminum chloride phthalocyanine and methylene blue in in vivo assays. Methods Fifty-six male Wistar rats were divided into two groups; one submitted to PDT and the other submitted to the photosensitizers without their photoactivation (control). The photosensitizers were applied to the dura mater after laminectomy at the T10 level. The methods used for assessment were the Basso, Beattie and Bresnahan (BBB) functional evaluation scale and study of the dura mater by light microscopy. Results No changes in motor activity were observed in the animals submitted to PDT compared to control. Histological and pathological evaluation did not show any differences between the group exposed to activated photosensitizers and the control group with regard to the inflammatory process and tissue necrosis. Conclusion The joint use of PDT with the photosensitizing pharmaceuticals aluminum chloride phthalocyanine and methylene blue did not induce any clinical neurotoxic effects or histological changes in the dura mater of the animals studied. Level de evidence V; Expert Opnion.